2017
DOI: 10.18632/oncotarget.20957
|View full text |Cite
|
Sign up to set email alerts
|

Specific role of RhoC in tumor invasion and metastasis

Abstract: Rho GTPases are regulators of many cellular functions and are often dysregulated in cancer. However, the precise role of Rho proteins for tumor development is not well understood. In breast cancer, overexpression of RhoC is linked with poor prognosis. Here, we aim to compare the function of RhoC and its homolog family member RhoA in breast cancer progression. We established stable breast epithelial cell lines with inducible expression of RhoA and RhoC, respectively. Moreover, we made use of Rho-activating bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 56 publications
6
29
0
Order By: Relevance
“…RhoA or RhoC have been described to increase cell growth 18,20,21 . However, their stable overexpression may also lead to a decrease in cell growth caused by the profound changes in the cytoskeleton 22,23 , which is accordance with our results.…”
Section: Stable Overexpression Of Wild Type or Dominant Negative Mutasupporting
confidence: 92%
“…RhoA or RhoC have been described to increase cell growth 18,20,21 . However, their stable overexpression may also lead to a decrease in cell growth caused by the profound changes in the cytoskeleton 22,23 , which is accordance with our results.…”
Section: Stable Overexpression Of Wild Type or Dominant Negative Mutasupporting
confidence: 92%
“…Previously, we reported that CNF1 increased prostate cancer cell migration and invasion to promote prostate cancer metastasis through activating Cdc42, 6 and CNF1 reduced macrophage phagocytosis to induce inflammation during acute UTIs partially through Cdc42 38 . Schmidt reported that CNF1 enhanced breast cancer cell invasion through activating RhoC 39 …”
Section: Discussionmentioning
confidence: 91%
“…For in vitro immunomonitoring, blood was taken before vaccination (visit 2), and after the 4th, 6th and 11th vaccinations (visits 6, 8 and 13). Follow-up samples were obtained every third month up to 13 months postvaccination (visits [14][15][16][17]. The study started in March 2017 and was completed in March 2019.…”
Section: Study Design and Patientsmentioning
confidence: 99%